2006
DOI: 10.1063/1.2186973
|View full text |Cite
|
Sign up to set email alerts
|

Effects of depletion on the emission from individual InGaN dots

Abstract: We report a photoluminescence ͑PL͒ study of the effects of carrier depletion on the electronic states of InGaN quantum dots. Samples were fabricated into mesa devices with top Schottky contacts and back ohmic contacts. Submicrometer apertures were created lithographically. Capacitance-voltage measurements of the devices suggest that the dots are fully depleted when they are unbiased. Micro-PL studies of individual dots show narrow linewidths under zero or reverse bias conditions. Forward biasing of the junctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The InGaN quantum dots (QDs) structure is a low dimension confinement structure that has many unique physical properties [6][7][8]. InGaN QDs can be used in the active region of LDs and LEDs to improve their performance and the temperature stability of devices [9,10].…”
mentioning
confidence: 99%
“…The InGaN quantum dots (QDs) structure is a low dimension confinement structure that has many unique physical properties [6][7][8]. InGaN QDs can be used in the active region of LDs and LEDs to improve their performance and the temperature stability of devices [9,10].…”
mentioning
confidence: 99%
“…However, only a few recent studies have reported such measurements on GaN/AlN [57,58] and InGaN/GaN QDs [59,60]. It was found that a vertical electric field can result in an almost linear blue shift of the optical transition of up to 100 meV in GaN/AlN QDs [58] due to the partial compensation of the in-built field and the dominant effect from the induced permanent dipole.…”
Section: Quantum-confined Stark Effect (Qcse)mentioning
confidence: 99%